Synergistic effect of Mo2C micro-particles and SiC nanoparticles on irradiation-induced hardening in dispersion-precipitation strengthened NiMo alloys. (December 2020) - Yang, Chao; Wei, Tao; Zhu, Guoliang; Shu, Da; Ju, Jiang; Zhou, Wenzhe; Dong, Anping; Sun, Baode; Ionescu, Mihail
Abstract: The mechanism for outstanding resistance to He-ion irradiation-induced hardening of a novel dispersion-precipitation strengthened NiMo alloy has been investigated. Microstructural observations show the interface between Mo2 C micro-particles and Ni matrix and between SiC nanoparticles and Ni matrix can effectively trap He bubbles, thus synergistically inhibiting the formation and growth of the dissociated He bubbles in the Ni matrix. It suggests that the reasonable high amounts of well-dispersed Mo2 C micro-particles and SiC nanoparticles can effectively improve the inhibition efficiency of irradiation-induced hardening and are beneficial for the optimization and design of irradiation-resistant Ni-based alloys. Graphical abstract: The mechanism for outstanding resistance to He-ion irradiation-induced hardening of a novel dispersion-precipitation strengthened NiMo alloy has been investigated. Microstructural observations show the interface between Mo2 C micro-particles and Ni matrix and between SiC nanoparticles and Ni matrix can effectively trap He bubbles, thus synergistically inhibiting the formation and growth of the dissociated He bubbles in the Ni matrix. It suggests that the reasonable high amounts of well-dispersed Mo2 C micro-particles and SiC nanoparticles can effectively improve the inhibition efficiency of irradiation-induced hardening and are beneficial for the optimization and design of irradiation-resistant Ni-based alloys. Image, graphical abstract